Archaeology of households, kinship, and social change
1 online resource.
Keywords: "Archaeology of Households, Kinship, and Social Change offers new perspectives on the processes of social change from the standpoint of household archaeology. This volume develops new theoretical and methodological approaches to the archaeology of households pursuing three critical themes: household diversity in human residential communities with and without archaeologically identifiable houses, interactions within and between households that explicitly considers impacts of kin and non-kin relationships and lastly change as a process that involves the choices made by members of households in the context of larger societal constraints. Encompassing these themes, authors explore the role of social ties and their material manifestations (within the house, dwelling or other constructed space), how the household relates to other social units, how households consolidate power and control over resources, and how these changes manifest at multiple scales. The case studies presented in this volume have broader implications for understanding the drivers of change, the ways households create the contexts for change, and how households serve as spaces for invention, reaction, and/or resistance. Understanding the nature of relationships within households is necessary for a more complete understanding of communities and regions as these ties are vital to explaining how and why societies change. Taking a comparative outlook, with case studies from around the world, this volume will inform students and professionals researching household archaeology and be of interest to other disciplines concerned with the relationship between social networks and societal change"--